Differentiation of clinically relevant MucoralesRhizopus microsporusandR. arrhizusby matrix‐assisted laser desorption ionization time‐of‐flight mass spectrometry (MALDI‐TOF MS). Issue 7 (July 2015) - Dolatabadi, Somayeh; Kolecka, Anna; Versteeg, Matthijs; de Hoog, Sybren G.; Boekhout, Teun
Abstract : N/A: This study addresses the usefulness of matrix‐assisted laser desorption ionization time‐of‐flight (MALDI‐TOF) MS for reliable identification of the two most frequently occurring clinical species of Rhizopus, namely Rhizopus arrhizus with its two varieties, arrhizus and delemar, and Rhizopus microsporus. The test‐set comprised 38 isolates of clinical and environmental origin previously identified by internal transcribed spacer (ITS) sequencing of rDNA. Multi‐locus sequence data targeting three gene markers (ITS, ACT, TEF ) showed two monophylic clades for Rhizopus arrhizus and Rhizopus microsporus (bootstrap values of 99 %). Cluster analysis confirmed the presence of two distinct clades within Rhizopus arrhizus representing its varieties arrhizus and delemar . The MALDI Biotyper 3.0 Microflex LT platform (Bruker Daltonics) was used to confirm the distinction between Rhizopus arrhizus and Rhizopus microsporus and the presence of two varieties within the species Rhizopus arrhizus . An in‐house database of 30 reference main spectra (MSPs) was initially tested for correctness using commercially available databases of Bruker Daltonics. By challenging the database with the same strains of which an in‐house database was created, automatic identification runs confirmed that MALDI‐TOF MS is able to recognize the strains at the variety level. Based on principal component analysis, two MSP dendrograms were created and showed concordance with the multi‐locus tree; thus, MALDI‐TOF MS is a useful tool for diagnostics of mucoralean species.